Effect of load balancing on punching shear stress and deflection of post tensioning flat slab with different grade of concrete - Padhiar, Kamal; C. D. Modhera, Dr; A. K. Desai, Dr; S. A. Vasanwala, Dr (International Journal of Engineering and Technology, 2018)
Flat slabs are a widely adopted solution now a day for buildings, because of their economic and functional advantages. The main objective of this paper is to analysis of post tensioning flat slab by changing the different parameter such as span of slab, grade of concrete and load balancing and comparing the result such as deflection and punching shear. Grade of concrete and load balance directly influence to the deflection and punching shear of flat slab. So in this paper concrete grade varies M-35 to M-50 is considered and load balance varies from minimum 25% to maximum 100% is considered. The use of ADAPT-PT builder 2015 is recommended because of its friendly use and quick calculation capabilities. Use of the ACI Code equivalent frame method of analysis was performed using said software.Â Â